Safety and Immunogenicity of a Respiratory Syncytial Virus Prefusion F (RSVPreF3) Candidate Vaccine in Older Adults: Phase 1/2 Randomized Clinical Trial. (29th July 2022) - Leroux-Roels, Isabel; Davis, Matthew G; Steenackers, Katie; Essink, Brandon; Vandermeulen, Corinne; Fogarty, Charles; Andrews, Charles P; Kerwin, Edward; David, Marie-Pierre; Fissette, Laurence; Vanden Abeele, Carline; Collete, Delphine; et al.
Abstract: Background: The aim of this study was to investigate safety and immunogenicity of vaccine formulations against respiratory syncytial virus (RSV) containing the stabilized prefusion conformation of RSV fusion protein (RSVPreF3). Methods: This phase 1/2, randomized controlled, observer-blind study enrolled 48 young adults (YAs; aged 18–40 years) and 1005 older adults (OAs; aged 60–80 years) between January and August 2019. Participants were randomized into equally sized groups to receive 2 doses of unadjuvanted (YAs and OAs) or AS01-adjuvanted (OAs) vaccine or placebo 2 months apart. Vaccine safety and immunogenicity were assessed until 1 month (YAs) or 12 months (OAs) after second vaccination. Results: The RSVPreF3 vaccines boosted humoral (RSVPreF3-specific immunoglobulin G [IgG] and RSV-A neutralizing antibody) responses, which increased in an antigen concentration-dependent manner and were highest after dose 1. Compared to prevaccination, the geometric mean frequencies of polyfunctional CD4 + T cells increased after each dose and were significantly higher in adjuvanted than unadjuvanted vaccinees. Postvaccination immune responses persisted until end of follow-up. Solicited adverse events were mostly mild to moderate and transient. Despite a higher observed reactogenicity of AS01-containing vaccines, no safety concerns were identified for any assessed formulation. Conclusions: Based on safety and immunogenicity profiles, the AS01E -adjuvanted vaccine containing 120 μg of RSVPreF3 was selected for further clinical development. Clinical Trials Registration: NCT03814590. Abstract : Vaccine formulations against respiratory syncytial virus (RSV) containing the stabilized prefusion conformation of RSV fusion protein (RSVPreF3) were well tolerated and immunogenic. Based on safety/immunogenicity profiles, the AS01E -adjuvanted vaccine containing 120 μg of RSVPreF3 was selected for further clinical development.